PENERAPAN MODEL PEMBELAJARAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR - Nahrowi Nahrowi (Saintifika, 2018)
Abstract: This study aims to improve the quality of education by making changes towards improvements to students' mathematics learning activities and outcomes by applying the Realistic Mathematics Learning model. This research was conducted in class X SMA Negeri Rambipuji in the even semester from April 19 to May 17 2016, with 32 students. This research is a classroom action research (PTK) which consists of 2 cycles with 4 stages, namely planning, implementing, observing and reflecting. Activity data were collected through observation at each lesson and learning outcomes were obtained through tests at the end of each cycle. Based on the data analysis, it was found that student activity increased the percentage of cycle I and cycle II, namely 68% and 82%. Meanwhile, the learning outcomes increased by 61% and 89%. From the results of this study, it can be concluded that the application of a realistic mathematics learning model can increase the activity and learning outcomes of class X SMA Negeri Rambipuji on the subject of cubes and blocks for the 2017/2018 academic year. Keywords: Realistic Mathematics Learning; Activities; Learning Outcomes